Host plant resistance to Radopholus similis in a diploid banana hybrid population - Dochez, C.; Tenkouano, A.; Ortíz, R.; Whyte, J.; Waele, D. de (Brill, 2009)
The objective of the research was to study the genetics of host plant resistance toRadopholus similisin a diploid bananapopulation. Screening of a hybrid population and determination of the segregation ratios can provide information on the inheritanceand number of alleles controlling this trait in banana. The diploid banana hybrid population used was derived by crossing the diploidhybrids TMB2x 6142-1 and TMB2x 8075-7. The diploid banana hybrid population was evaluated with the individual root inoculationmethod using anR. similispopulation from Namulonge, Uganda. Of the 81 hybrids evaluated, 37 hybrids were resistant, 13 hybridswere partially resistant and 31 hybrids were susceptible toR. similis. After chi-square analysis, the results indicated that resistance toR. similisis controlled by two dominant genes,AandB, both with additive and interactive effects, whereby recessivebbsuppressesdominantA